Broadband measurement of high permittivity at millimetre‐wave frequencies. Issue 9 (1st April 2016) - Hong, Y.‐P.; Salter, M.J.; Lee, D.‐J.
Abstract : In this Letter, a method for the broadband measurement of complex permittivity using a quasi‐optical technique is presented. After calibration of the quasi‐optical system, the material under test is inserted into the system and S ‐parameters are measured from 220 to 330 GHz using a vector network analyser. An extraction method is then applied to calculate the complex permittivity. The permittivity measurements are validated by comparing with a well‐established extraction method and the comparison shows good agreement.